EFEITO DA ÉPOCA DE SEMEADURA NA PRODUÇÃO DE GRÃOS DE HÍBRIDOS DE MILHO - Siega, Paula Cristina (2015)
The purpose of this study was to evaluate the behavior of maize cultivars, cultivated in different periods of sowing in Guarapuava-PR. The research was developed in the experimental farm of IAPAR, in the city of Guarapuava-PR. The experimental delimitation was in random groups of factorial 10 x 4 x 2, being ten maize cultivars, four sowing dates (14/09, 28/09, 18/10, 02/11), in two agricultural crops (2010/2011 and 2011/2012). The agronomical characteristics evaluated were: productivity (kg ha?¹); weight of one thousand seeds; damaged seeds; index of ears; number of seeds per ear; number of lines of seeds per ear; number of seeds per line. The evaluated characteristics were subject to analyses of variance and average tests (Tukey, probability of 5%). The analyses were performed with the statistical software SISVAR. The maize cultivars presented different behaviors in performance to most of the related variables. It was observed more productivity and weight in one thousand seeds of the second growing crop. For the remaining analyzed variables the best results were from the first growing crop. There were variations in the analyzed variables between the hybrids in the different periods of sowing, except for the number of ears, which practically didn`t chance. For the variable, lines of seeds per ear, that was no differences between the harvests.